2019
DOI: 10.1111/and.13435
|View full text |Cite
|
Sign up to set email alerts
|

Morphological reseach on expression of inflammatory mediators in murine models of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) induced by T2 antigen

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common clinical syndrome with unknown aetiology. In this study, we used the T2 peptide in C57BL/6 (B6) mice and Sprague Dawley (SD) rats model during different stages. We sought to understand the role of CD4 + T cells and macrophages in CP/CPPS. A total of 16 B6 mice and 18 SD rats were divided into five groups: B6-naïve (n = 6), B6 model (n = 10), SD-naïve (n = 6), SD-45-day model (n = 6) and SD-56-day model (n = 6). The B6 model group was subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The role of CXCL10 in macrophage recruitment has been reported as well ( 33 , 46 ). Macrophages are key factors in the development of CP/CPPS ( 15 , 47 ). However, little is known about the effect of CXCL10 on macrophage function in the EAP model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of CXCL10 in macrophage recruitment has been reported as well ( 33 , 46 ). Macrophages are key factors in the development of CP/CPPS ( 15 , 47 ). However, little is known about the effect of CXCL10 on macrophage function in the EAP model.…”
Section: Discussionmentioning
confidence: 99%
“…The EAP model, a valid model for CP/CPPS, shares some histologic features with CP/CPPS in humans, which is defined by a florid intraprostatic leukocyte infiltrate, including CD4+ and CD8+ T cells, B cells, dendritic cell, and macrophages ( 12 ). Moreover, the intraprostatic inflammatory infiltrate in the EAP model is characterized by CD4+ T cells and macrophages ( 13 , 14 ), suggesting its vital roles in the development of EAP ( 15 ). These cells could interact with other immune and resident cells, including epithelial and stromal cells by secreting cytokines and chemokines, leading to a boost in the production of proinflammatory cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…The study found CD4 + T cells and macrophages are key factors in the development of CP/CPPS [45]. Increased inflammasome may be a possible mechanism of CP/CPPS, and inhibiting the inflammasome-related pathway may be a new therapeutic approach [46].…”
Section: Discussionmentioning
confidence: 96%
“…The study found CD4 + T cells and macrophages are key factors in the development of CP/CPPS. [53] Increased inflammasome may be a possible mechanism of CP/CPPS, and inhibiting the inflammasome-related pathway may be a new therapeutic approach. [54] Some studies revealed that inflammasome might be a target for pain therapy.…”
Section: Discussionmentioning
confidence: 99%